Gas accretion in Milky Way-like galaxies: Temporal and radial dependencies - Nuza, Sebastian Ernesto (2019)
One of the fundamental assumptions of chemical evolution models (CEMs) of the Milky Way (MW) and other spirals is that higher gas accretion rates are expected in the past, and in the inner regions of the Galaxy. This leads to the so-called 'inside-out disc formation scenario'. Yet, these are probably the most unconstrained inputs of such models. In this paper, we aim at investigating these main assumptions by studying how gas is accreted in four simulated MW-like galaxies assembled within the ΛCDM scenario. The galaxies were obtained using two different simulation techniques, cosmological setups, and initial conditions. Two of them are MW candidates corresponding to the chemodynamical model of Minchev, Chiappini & Martig (known as MCM) and the Local Group cosmological simulation of Nuza et al. We investigate vertical and radial gas accretion on to galaxy discs as a function of cosmic time and disc radius. We find that accretion in the MW-like galaxies seem to happen in two distinct phases, namely, an early, more violent period; followed by a subsequent, slowly declining phase. Our simulations seem to give support to the assumption that the amount of gas incorporated into the MW disc exponentially decreases with time, leading to current net accretion rates of 0.6-1 M⊙ yr-1. In particular, accretion time-scales on to the simulated thin-disc-like structures are within ∼5-7 Gyr, consistent with expectations from CEMs. Moreover, our simulated MW discs are assembled from the inside-out with gas in the inner disc regions accreted in shorter time-scales than in external ones, in qualitative agreement with CEMs of the Galaxy. However, this type of growth is not general to all galaxies and it is intimately linked to their particular merger and gas accretion history.